2011
DOI: 10.1007/s10456-011-9206-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aldose reductase prevents angiogenesis in vitro and in vivo

Abstract: We have recently shown that aldose reductase (AR, EC 1.1.1.21) a nicotinamide adenine dinucleotide phosphate-dependent aldo-keto reductase, known to be involved in oxidative stress-signaling, prevents human colon cancer cell growth in culture as well as in nude mice xenografts. Inhibition of AR also prevents azoxymethane-induced aberrant crypt foci formation in mice. In order to understand the chemopreventive mechanism(s) of AR inhibition in colon cancer, we have investigated the role of AR in the mediation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 51 publications
0
52
0
1
Order By: Relevance
“…Blockade or genetic deficiency of aldose reductase reverses the excessive angiogenesis associated with vascular retinopathy (Fu et al, 2012;Obrosova and Kador, 2011). Interestingly, aldose reductase inhibitors also decrease VEGFstimulated angiogenesis, suggesting a role for polyol pathway flux in normal angiogenic functions (Tammali et al, 2011).…”
Section: Polyol Pathwaymentioning
confidence: 99%
“…Blockade or genetic deficiency of aldose reductase reverses the excessive angiogenesis associated with vascular retinopathy (Fu et al, 2012;Obrosova and Kador, 2011). Interestingly, aldose reductase inhibitors also decrease VEGFstimulated angiogenesis, suggesting a role for polyol pathway flux in normal angiogenic functions (Tammali et al, 2011).…”
Section: Polyol Pathwaymentioning
confidence: 99%
“…Various investigators have presented evidence that antioxidants and natural polyphenolic compounds with antioxidant properties could prevent neovascularization in experimental animals (Dorrell et al, 2009; Chen, Li, Xing, & Cao, 2008; Tan et al, 2008; Kim et al, 2007; Kim et al, 2009; Keshavarz et al, 2009). Recently our lab has demonstrated that inhibition of aldose reductase (AR), a glucose and lipid aldehyde metabolizing enzyme, has anti-inflammatory and anti-oxidative properties and could prevent cancer angiogenesis in-vitro and in-vivo (Tammali, Reddy, Srivastava, & Ramana, 2011; Yadav et al, 2009a; Yadav et al, 2009b; Yadav, Srivastava, & Ramana, 2010). However, role of AR inhibition in diabetes-induced retinal neovascularization is not known.…”
Section: Introductionmentioning
confidence: 99%
“…This idea was abetted by the discovery of a small subset of stromal spindle cells expressing CD133 and CD34 in angiofibromas, which suggests tumors promoting subepithelial resident cells to transit towards endothelial cell phenotypes [72] . Endothelial progenitor cells were then shown to lose, in a process related to high proliferation [73] , the expression of CD133 during their differentiation into vascular cells, while the expression of CD34 was increased [74][75][76] . Considering that CD31-positive cells have been designated as mature endothelial lineage promoting microvessels [77] , vascular smooth muscle cells were found to increase the expression of CD31 during their differentiation process, whilst a simultaneous decrease of CD133 and CD34 progenitor markers was previously observed [78,79] .…”
mentioning
confidence: 99%